Secular changes in body fat patterning in children and adolescents of Zaragoza (Spain), 1980–1995 - Moreno, LA; Fleta, J; Sarría, A; Rodríguez, G; Gil, C; Bueno, M (International Journal of Obesity, 2001)
To examine whether children and adolescents of Zaragoza (Spain) are becoming centrally obese to a greater extent than would be predicted by their relative body weights. Two cross-sectional surveys conducted in 1980 and 1995. The samples selected for the 1980 and 1995 surveys comprised 1553 and 701 male children, and 1311 and 659 female children, respectively, with ages ranging from 6.0 to 14.9 y. We measured four skinfold thicknesses (biceps, triceps, subscapular, suprailiac) and calculated some indices of fat patterning: triceps/subscapular skinfolds (T/SS), biceps+triceps/subscapular+suprailiac skinfolds (B+T/SS+SI), and (subscapular+suprailiac/biceps+triceps+subscapular+suprailiac skinfolds)x100 (trunk-to-total skinfolds %). In males, B+T/SS+SI, and trunk-to-total skinfolds % showed a significant trend to a central pattern of fat distribution from 1980 to 1995, at the ages of 6.5-11.5 y. In females, B+T/SS+SI and trunk-to-total skinfolds % showed a significant trend to a central pattern of fat distribution from 1980 to 1995, at the ages of 6.5 and 7.5 y. Similar results were obtained when we adjusted for BMI values. We have observed a trend to a central pattern of adipose tissue distribution, especially in males and at the youngest ages studied (6-11 y in males, and 6-7 y in females). These observations were independent of trends in BMI.